Conformity of Indonesian Islamic bank CSR practices with maqashid shariah rules - Prasojo, Prasojo; Muhfiatun, Muhfiatun; Syarifah, Lailatis; Rosman, Romzie (Emerald Publishing, 2025)
Purpose – This research aims to examine the connection between corporate social responsibility (CSR) disclosure and the performance of Islamic banks (IBs), considering their obligation to comply with Shariah principles and promote social welfare. Specifically, it seeks to assess the extent to which CSR activities of IBs align with the objectives of Maqasid Shariah. Design/methodology/approach – Conducting content analysis to examine the annual reports of 12 IBs in Indonesia. Findings – The findings show that these banks successfully align their CSR activities with the five key elements of maqasid shariah: faith, life, intellect, progeny and wealth. This alignment significantly enhances community welfare, economic stability and customer satisfaction. It also boosts stakeholder legitimacy, leading to greater satisfaction and loyalty, which supports the long-term performance of the banks. Research limitations/implications – This study delves into the CSR activities of IBs in Indonesia. It is essential to note that the findings may not be universally applicable to different countries due to variations in culture, educational levels and Muslim minorities in various regions. Practical implications – The practical implications of CSR key activities serve as valuable guidelines for IBs, aiding them in enhancing initiatives and formulating CSR activities aligned with maqasid shariah principles. Social implications – CSR practices aligned with maqasid sharia principles exert a significant positive impact on mitigating environmental, economic and social challenges. Originality/value – This research offers a concept of Islamic bank CSR activities based on the principles of maqasid shariah, along with a framework to map these activities to the elements of maqasid shariah. In addition, this research introduces a unique methodology, using content analysis to assess the alignment of CSR with maqasid shariah